Original researchCharacteristics of obstetric fistulas and the need for a prognostic classification system - Karateke, Ates; Cam, Cetin; Ozdemir, Arman; Guney, Buhara; Vatansever, Dogan; Celik, Cem (Archives of Medical Science, 2010)
Introduction: To evaluate the need for a prognostic classification system for obstetric fistula (OF) with the data obtained by a voluntarily action for OF repair in a regional hospital and Niger, Africa. Material and methods: Obstetric fistula (OF) characteristics of 51 women with vesicovaginal fistula in a fistula campaign in Maradi Regional Hospital, Niger were evaluated. Initial basic gynecological examination, methylene blue (MBT) test and direct cystoscopy were used to describe the characteristics of the lesions. Demographic and clinical data were compared with the existing literature. Results: In 31 (60 %) cases were the sizes of the fistula greater than 4 cm. The urethra was circumferentially lost in 8 (15.7%) women. In 18 (35.3%) women the trigone was involved. Extensive fibrosis was present in 10 (19.6%) patients. Only in 11 (21.6%) patients without any obliterating scarring, neither the trigone nor urethra were damaged. Five (9.8%) patients had severe infection. Five (9.8%) had multiple lesions. Thirty-four (66.6%) had a history of at least one previous attempt for fistula repair. A significant proportion of women were divorced or abandoned from their husband, and socially isolated. Conclusions: A simple, reproducible and universally accepted scientific classification or staging system for OF dealing with outcomes rather than anatomic landmarks should replace the present proposed classification systems for prognostic and ethical purposes.